TB-09 MRNA-SEQ FOR PERICYTES FROM IN VITRO BRAIN METASTASIS AND BLOOD-BRAIN BARRIER MODEL. (16th December 2019) - Ujifuku, Kenta; Fujimoto, Takashi; Sato, Kei; Morofuji, Yoichi; Muto, Hideki; Masumoto, Hiroshi; Nakagawa, Shinsuke; Niwa, Masami; Matsuo, Takayuki
Abstract: BACKGROUND: Metastatic brain tumors associated with poor prognosis and limited treatment options. The blood-brain barrier (BBB) is supposed to play a major role in brain metastasis. However, little is known about the role of pericytes in brain metastasis formation. This study aimed to reveal the expression profile of interaction between pericytes, endothelial cells, and cancer cells. METHODS: The Institutional review board approved this study. We established an in vitro BBB model with rat primary cultured BBB-related cells (endothelial cells and pericytes) and investigated the gene expression of pericytes under the lung cancer cell's coculture circumstances. Pericytes showed inhibition of the KNS-62 cell proliferation significantly (p < 0.05). RNA was extracted from the pericytes using miRNeasy mini kit. Complementary DNA library preparation was performed with QuantSeq 3 'mRNA-Seq Library Prep Kit. RNA-seq was performed with MiSeq using MiSeq Reagent Kit v3. Sequencing reads were analyzed on the Maser (TopHat2-CuffLinks2-CummeRbund, TopHat2-HTSeq) and TCC-GUI (EdgeR, DESeq, baySeq) platform. Enrichment analysis was performed at Metascape, and the results were analyzed concerning the OMIM and KEGG databases. RESULT: The RIN value of RNA < 8.0 was confirmed. Data quality was acceptable in Fast QC analysis. In TCC differential expressed gene (DEG) analysis, cluster analysis showed that the influence of pericyte lot difference was stronger than the change between cell lines and control. Therefore, lot-specific DEG analysis was performed; the data were pretreated and re-analyzed to try to identify genes involved in the suppression of cancer cell growth. DISCUSSION: This study revealed that some expression profiles of brain pericytes implemented in the prevention of metastatic lung cancer cell proliferation in the brain. Pericytes exert an anti-metastatic effect and thus have the potential for the preventive treatment of brain metastasis.